2018
DOI: 10.1055/a-0647-1709
|View full text |Cite
|
Sign up to set email alerts
|

Screening of esophageal varices in children using esophageal capsule endoscopy: a multicenter prospective study

Abstract: Background Esophagogastroduodenoscopy (EGD) is the standard method for diagnosis of esophageal and gastric varices in children. In this prospective study we evaluated the use of PillCam esophageal capsule endoscopy (ECE) in pediatric patients. Methods Patients aged 7 to 18 years presenting with portal hypertension and/or cirrhosis underwent ECE (PillCam ESO 2, Given Imaging Ltd.) followed by EGD. Results 102 patients were screened, 81 (52 boys; mean age 13.96 ± 0.25 years) were included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Table 1 provides a summary of specific characteristics of these studies and also our present case report, including demographic and risk factors, chief complaints, physical examinations, abdominal radiological findings, endoscopy for extraction of the denture if done, location of obstruction or perforation, and kind of surgery. According to our report and the six previous reports mentioned [ 9 – 14 ], if there is evidence of duodenal perforation or if the endoscope is unable to remove the foreign body early, surgical intervention is recommended.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Table 1 provides a summary of specific characteristics of these studies and also our present case report, including demographic and risk factors, chief complaints, physical examinations, abdominal radiological findings, endoscopy for extraction of the denture if done, location of obstruction or perforation, and kind of surgery. According to our report and the six previous reports mentioned [ 9 – 14 ], if there is evidence of duodenal perforation or if the endoscope is unable to remove the foreign body early, surgical intervention is recommended.…”
Section: Discussionmentioning
confidence: 58%
“…There are very rare case reports on denture ingestion-induced duodenal obstruction and perforation, and we found six previous reports to use in our review of the literature, as shown in Table 1 [ 9 – 14 ]. The aim of this study was to report a rare case of accidental ingestion of a dental prosthesis with duodenal obstruction and perforation that could not be treated with endoscopic management and was managed with duodenal kocherization and gastrostomy.…”
Section: Introductionmentioning
confidence: 99%
“…During the endoscope testing, it was possible to observe the peristaltic contraction of the esophagus in various places due to the possibility of adjusting the position to different parts of the esophagus by a lead-in cable. Since the thickness of the lead-in cable was only 1.2 mm, the physiological activity of the esophagus was just minimally influenced.Figures 4-9also document that the imaging properties of the prepared capsule endoscope are comparable to the commercial capsule endoscope systems 20.…”
mentioning
confidence: 68%
“…Although the conventional EGD represents the gold standard and the preferred endoscopic techniques for the study of the esophagus, some esophageal diseases may be detected using a capsule device. 20,21 In this paper, we describe the fabrication method, properties, and results from the testing of the new capsule endoscope for retrograde imaging of the esophagus. By precise design of the optical input of the endoscopic module, we were able to suppress the effects of the internal light reflections, which are a common problem when lighting and imaging equipment are situated under the same dome.…”
Section: Resultsmentioning
confidence: 99%
“…However, none have been thoroughly evaluated through prospective studies, and their predictive accuracy is in question, leaving gastroscopy as the chief method of diagnosis (Garcia-Tsao et al 2007. Capsule endoscopy is a promising means of direct variceal observation, but its cost is prohibitive (Lapalus et al 2009;Sacher-Huvelin et al 2015;Cardey et al 2019).…”
Section: Discussionmentioning
confidence: 99%